2001
DOI: 10.4049/jimmunol.166.3.1457
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Expression of the C-C Chemokine Receptor CCR3 in Human Airway Epithelial Cells

Abstract: Chemokine-induced eosinophil chemotaxis is mediated primarily through the C-C chemokine receptor, CCR3. We have now detected CCR3 immunoreactivity on epithelial cells in biopsies of patients with asthma and other respiratory diseases. CCR3 mRNA was detected by Northern blot analysis after TNF-α stimulation of the human primary bronchial epithelial cells as well as the epithelial cell line, BEAS-2B; IFN-γ potentiated the TNF-α-induced expression. Western blots and flow cytometry confirmed the expression of CCR3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
64
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 27 publications
7
64
1
1
Order By: Relevance
“…Our data showing that murine CCR3 is predominantly expressed by eosinophils are consistent with previous studies (19,20). These observations suggest that leukocyte recruitment in chronic allergic inflammation is orchestrated, at least in part, via CCR3 signaling in eosinophils, although we cannot exclude signal transduction events in other cells such as basophils and epithelial cells, because they have been shown to express low levels of CCR3 at least in the human system (21,22). Interestingly, only eosinophil trafficking is impaired in the eotaxin-1͞2-deficient mice, suggesting that other CCR3 ligands provide sufficient stimulation to induce the infiltration by other cell types.…”
Section: Discussionsupporting
confidence: 82%
“…Our data showing that murine CCR3 is predominantly expressed by eosinophils are consistent with previous studies (19,20). These observations suggest that leukocyte recruitment in chronic allergic inflammation is orchestrated, at least in part, via CCR3 signaling in eosinophils, although we cannot exclude signal transduction events in other cells such as basophils and epithelial cells, because they have been shown to express low levels of CCR3 at least in the human system (21,22). Interestingly, only eosinophil trafficking is impaired in the eotaxin-1͞2-deficient mice, suggesting that other CCR3 ligands provide sufficient stimulation to induce the infiltration by other cell types.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, cell surface binding of both eotaxin-3 and IP-10 to BEAS-2B cells was equally and completely sensitive to pronase pretreatment, suggesting that the non-GAG cell binding sites of eotaxin-3 may be mediated by the protein component or non-GAG sugar moieties of cell surface proteoglycans, or by entirely different cell surface proteins. It has been shown that BEAS-2B cells express low levels of CCR3 receptor on their surface [36]. However, we found that addition of an anti-CCR3 blocking mAb to BEAS-2B cells during IL-4 stimulation did not alter the eotaxin-3 surface binding (data not shown), which argues against a significant role of CCR3 in eotaxin-3 cell surface association in airway epithelial cells.…”
Section: Discussioncontrasting
confidence: 53%
“…In contrast, surface expression of CCR3 or CX3CR1 was similar in iDCs and Hi-DCs. Lack of correlation between mRNAs and protein expression was observed in cytokine-stimulated human airway epithelial cells, and the possibility of translational regulation of CCR3 by hypoxia was suggested (49). The increase in CCR2 surface expression was a novel finding and raised the question of the functional response of Hi-DCs to the chemokine receptor -specific ligands.…”
Section: Hypoxia and Differentiation Of Dendritic Cells Mol Cancer Rementioning
confidence: 98%